Impact of visceral obesity on postoperative outcomes in colorectal cancer: a systematic review and meta-analysis - Wang, Yulong; Liu, Xijuan; Feng, Xiao; Jiang, Xing; Huang, Lili (Frontiers in Oncology, 2025)
BackgroundThis systematic review and meta-analysis aimed to assess the impact of visceral obesity (VO) on postoperative outcomes in colorectal cancer (CRC) patients.MethodsPrimary studies were obtained from sources like Embase, PubMed, and Web of Science during the search, which ran until October 2024. Patients with colorectal cancer who had visceral obesity (VO) and those who did not were compared in terms of intraoperative conditions, postoperative outcomes, postoperative complications, and long-term prognoses, including overall survival (OS) and disease-free survival (DFS).Results5,756 individuals with VO and 5,373 patients without VO were among the 11,129 patients who had colorectal cancer resected. Patients with VO had higher conversion rates (p = 0.03), fewer lymph nodes removed (p = 0.05), and longer recovery times for bowel movements (p = 0.009). Furthermore, patients with VO had a considerably greater overall incidence of sequelae than those without (p = 0.0003), including anastomotic leaks (p = 0.01), intestinal obstruction (p = 0.0003), intra-abdominal abscesses (p = 0.004), wound infections (p < 0.00001), and pulmonary problems (p = 0.0003). OS and DFS, however, did not differ between the two groups (p > 0.05).ConclusionsColorectal cancer patients with VO who have surgery tend to have fewer lymph nodes taken, more problems after surgery, and a higher rate of switching to open surgery.